SENI RUPA SEBAGAI MEDIA PENYADARAN - Rahmat Jabaril (Jurnal Budaya Nusantara, 2020)
Fine Art as a form of expression of artists, certainly not like economists who need advantages in currency values. Art is not likely to be intervened by fields of pragmatic size. Then it will be so difficult to place art as part of the aesthetic element. So, in this case, we can see the strengths that are in the art itself. Art as a matter of which considered unconstitutional is certainly very paradoxical when it is part of standard rules. So when art works, it becomes part of aesthetic polarization and not being as a reading room in the future. The method used in this study is study of literature with an emphasis on the philosophy of art that gives bargaining power to change in thinking, freedom of interpretation Then The aim of study of literature is to gain an understanding that art gives its weight in thinking about renewal art with a constructive approach through aesthetic understanding. For this reason, fine arts should see forms of visualization as a form of social reality. With it, the artist must be able to create novelty as well as from ethics, aesthetics, and the philosophy of art itself. Without it, the existence of artists cannot be expected to advance the world of art, if the artists themselves lack understanding of the principles in creating fine arts. Therefore, in this paper, the author is obliged to offer solutions, as an effort to improve the quality of the concept of works and at the same time associated with the cultural movement in the public.